Early Marriage as a Risk Factor for Anemia and Low Birth Weight During the Covid-19 Pandemic - Lalu Juntra Utama; Widarta Widarta; I Nyoman Adiyasa; Reni Sofiyatin; I Gde Narda Widiada; Lina Yunita; Kiki Kristiandi (Sarana Ilmu Indonesia (salnesia), 2023)
Early marriage has a risk impact on the fetus and pregnant women. This triggers anemia and chronic lack of energy in the mother and has an impact on the growth of the fetus and children born with low birth weight. Law Number 16 of 2019 stipulates a basic age of 19 years for marriage for both men and women. This study is a community based cross-sectional study conducted in April 2022. Random sampling was used to select 117 samples. Data on the baby's weight, anemia, and mother's arm circumference were obtained from the 2019-2021 Health Center cohort data. Socio-demographics were collected using a structured questionnaire. Babies born to mothers aged 19 years and under were used as research subjects. The results confirm that the covid 19 pandemic, place of residence, education level, and work status are related to the incidence of early marriage in women. Education level has a significant impact on changes in birth weight in mothers who early marriage during the Covid-19 with p-value<0,05. There was no significant relationship found that women who were married at the age of 19 and under had a risk of suffering from anemia, chronic lack of energy and low birth weight with p-value>0,05. Education level has a significant impact on changes in birth weight in mothers who early marriage during the Covid-19. The use of other samples as controls may be needed at the time of further research so that the results obtained become a comparison of intervention cases.